Biofabrication of Gelatin Tissue Scaffolds with Uniform Pore Size via Microbubble Assembly. Issue 11 (21st August 2019) - Bayram, Cem; Jiang, Xinyue; Gultekinoglu, Merve; Ozturk, Sukru; Ulubayram, Kezban; Edirisinghe, Mohan
Abstract: The control of pore size and uniform porosity remains as an important challenge in gelatin scaffolds. The precise control in building blocks of tissue scaffolds without any additional porogen is possible with costly equipment and techniques, though some pre‐requirements for polymeric material, such as photo‐polymerizability or sintering ability, may be needed prior to construction. Herein, a method for the fabrication of gelatin scaffolds with homogenous porosity using simple T‐junction microfluidics is described. The size of the microbubbles is precisely controlled with 5% deviation from the average. Porous gelatin scaffolds are obtained by building‐up the monodispersed microbubbles in dilute cross‐linker solutions. The effect of cross‐linker density on pore diameter is also investigated. After cross‐linking, pore size of the resultant five scaffold groups are precisely controlled as 135 ± 11, 193 ± 11, 216 ± 9, 231 ± 5, and 250 ± 12 µm. Porosity ratios above 65% are achieved in every sample group. According to the cell culture experiments, structures support high cell adhesion, viability, and migration through the porous network via interconnectivity. This study offers a practical and economical approach for the preparation of porous gelatin scaffolds with homogenous porosity which can be utilized in diverse tissue engineering applications. Abstract : Uniform porosity is a fundamental feature affecting cell growth, migration and differentiation. Gelatin scaffolds having homogeneous pore diameter with a narrow size distribution are fabricated using microbubbles generated by T‐junction microfluidics. This study emphasizes that scaffolds made by the bottom‐up assembly of microbubbles can be used in a wide range of applications, especially in pore‐size dependent studies.